OPTIMASLISASI PRODUK CAMILAN DENGAN MANAJEMEN PRODUKS DAN PEMASARAN MELALUI MEDIA SOSIAL - Naila Kumala; Dyah Purwita Wardani SWW (Politeknik Negeri Sriwijaya, 2022)
Micro-enterprises in Indonesia have experienced significant development from time to time. Business people are able to produce various types of diverse products. Micro, small and medium enterprises (MSMEs) are one of the breakthroughs in increasing economic growth in the community. Along the way, the development of micro-enterprises was also followed by the development of a marketing system that entered the realm of digital media. This aside from being a factor capable of breaking the tide of the market, on the other hand, it is also an obstacle for some micro-enterprises. Lack of knowledge in digital and marketing fields has resulted in some micro-enterprises being unable to compete in conditions of competitive market competition. The purpose of the community service wrapped in the Kuliah Kerja Nyata (KKN) program is to provide assistance and training to one of the snack MSMEs in Karangsari Village, Banyuwangi Regency so that MSMEs can know and understand good processed products and digital market opportunities. This KKN activity can be completed well in its entirety. This can be indicated by the achievements that have been obtained, namely: fostered partners already have new product innovations and have and are able to print packaging logos on products. The fostered partners are also able to promote products by marketing through social media. It is hoped that with this assistance and training, micro business actors as partners will be able to become entrepreneurs and/or do business independently and be independent of their processed products. Keywords: MSMes, Mentoring and Training, Product Marketing